ISOLASI DAN KARAKTERISASI BAKTERI PENDEGRADASI HERBISIDA DIURON DAN BROMACIL DARI AREA PERKEBUNAN DI LAMPUNG - Nur Laili; Hartati Imamuddin (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Diuron and bromacil are a broad-spectrum herbicide that is widely used in some plantation at Lampung. The soil sample is collected from some locations such as at banana Plantation (NTF), pineapple plantation (GGPC) and sugarcase plantation (GM). The aims of the research was to know the isolation and characterization of diuron and bromacil degrading bacteria. The highest diuron resistant bacteria was found in GM soil sample and The highest bromacil resistant bacteria was found in NTF soil sample. The result showed that there are three isolates for diuron degradation and five isolates for bromacil degradation bacteria from NTF, GGPC and GM. These isolates were tested to explore their ability for diuron and bromacil degradation on different concentrations. Isolation of bacteria was tested by using enrichment culture method and degradation of diuron and bromacil were checked by using spectrophotometric method. Diuron and bromacil degradation by 5 consortium indicated that all of consorsia have the ability to degrade them.